Two-dimensional molybdenum carbide 2D-Mo2C as a superior catalyst for CO2 hydrogenation - Hui Zhou (Nature Portfolio, 2021)
The development of robust and efficient catalysts for CO2 hydrogenation to value-added chemicals is an urgent task. Here the authors report two-dimensional carbide catalyst based on earth-abundant molybdenum that hydrogenates CO2 with high activity, stable performance and tunable selectivity.